1983
DOI: 10.1136/bjo.67.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Common causes of blindness and visual handicap in the west of Scotland.

Abstract: SUMMARY An analysis of blind registration forms was made to determine the commonest causes of blindness in the west of Scotland. It was found that the leading causes of blindness in order of frequency of incidence were senile macular degeneration, glaucoma, cataract, diabetic retinopathy, and myopic degeneration. Diabetic retinopathy was the leading cause of blindness among persons of working age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
128
1
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(138 citation statements)
references
References 0 publications
7
128
1
2
Order By: Relevance
“…In the west of Scotland DR was the fourth cause of blindness (8.5% of total) in 1980, and the most common cause in working age (20-64 years) [31]. In County Avon, in 1984 to 1986, DR came third (6.0%) and again the main cause among 30 to 69 year olds [32].…”
Section: Diabetes-related Blindnessmentioning
confidence: 99%
“…In the west of Scotland DR was the fourth cause of blindness (8.5% of total) in 1980, and the most common cause in working age (20-64 years) [31]. In County Avon, in 1984 to 1986, DR came third (6.0%) and again the main cause among 30 to 69 year olds [32].…”
Section: Diabetes-related Blindnessmentioning
confidence: 99%
“…In the United Kingdom Sorsby (1972) found that diabetic retinopathy was the single leading cause of new blindness in England and Wales in patients between ages 30 and 64, accounting for 15% of all new registered blindness. 10 years later Ghafour et al (1983) found that diabetic retinopathy was the most common cause of blindness in the age-group of 45-64 years in the west of Scotland, accounting for 10% of registered blindness, and at the same time Doesschate (1982) found diabetes to be the leading cause of blindness in the Netherlands, accounting for 21% of reported blindness. Sjølie and Green (1987) found the prevalence of blindness in a Danish population to be 5.9% in diabetics with a duration of more than 8 years and estimated the prevalence of blindness in diabetics to be 50-80 times higher than in the normal population.…”
Section: Visual Impairment In Diabeticsmentioning
confidence: 99%
“…1,2 Diabetic retinopathy is seen in most type I diabetics and 60% of type II diabetics 20 years after diagnosis. 3 Approximately 2% of the UK population have diabetes, of whom 200 000 have type I (insulin dependent) and more than 1 million have type II (non-insulin dependent).…”
Section: Introductionmentioning
confidence: 99%